The resistant ability to weevils and the characteristics of VrPDF1 gene of some mungbean cultivars (Vigna radiata L.Wilczek) - Thao, Hoàng Thị; Tường, Hồ Mạnh; Lan, Nguyễn Thị Ngọc; Thanh, Nguyễn Vũ Thanh; Sơn, Nguyễn Văn; Mậu, Chu Hoàng (Vietnam Journal of Biotechnology, 2016)
Plant defensins play a role against the seed-feeding insects. Defensin associates with the center of α-amylase activity in the gut of weevils, thus inhibiting the digestion of starch by weevils. In this study, the resistance of eight mungbean cultivars to weevils was evaluated by the method of artificial weevils infection. The Tam TH cultivar had lowest index of susceptibility to weevils (634.63) and DX22 cultivar had highest index (1058.72), and the highest resistance to weevils was found in Tam TH and DX22 was found to have the lowest resistance. VrPDF1 genes isolated from mungbean cultivars are 356 bp in length with two exons interrupted by an intron. The coding region of the VrPDF1 gene is 228 bp in length, encoding 75 amino acids. The comparative results of the nucleotide sequence of cDNA between Tam TH and DX22 showed that there was a difference in 13 nucleotides and comparison of amino acid sequences of the deduced protein indicated that there was a difference in 9 amino acids. Within the intron region of the VrPDF1 genes there was difference in 5 nucleotides. The genetic distance based on nucleotide sequences of the coding region of VrPDF1 gene of DX22 and seven other mungbean cultivars is 6.2% and based on the amino acid sequence deduced is 7.7%. The coding region of the VrPDF1 gene of DX22 was used to create a transformation vector aimed at creating weevil-resistant transgenic mungbean.